Molecular identification and phylogenetic reconstruction of two fiddler crabs (Uca forcipate and Uca triangularis). - Sapto Andriyono, ,- (IOP Publishing Ltd, 2019)
Fiddler crabs are one of the types of fauna that inhabit the mangrove ecosystem. They have an essential role in nutrient improvements in the mangrove substrate, besides increasing oxygenation, decomposition and percolation rate, and decreasing salinity and the sulfide substrate condition. This study performed the identification of two species based on their molecular qualities through COI gene markers. The samples were collected from Surabaya, Indonesia and their genomic DNA was extracted through DNA kit extraction at the Molecular Physiology Laboratory PKNU, Busan Korea. Based on the molecular identification in BLASTN, the two species confirmed were Uca forcipata and Uca triangularis with 99% certainty. The species were classified as an Asian fiddler crab species based on the phylogenetic tree featuring 59 species of fiddler crab from around the world.